Meningkatkan Kemampuan Dasar Literasi Dan Numerasi Melalui Kegiatan Market Day Bagi Anak Usia Dini Di SPS Melati II Desa Margasari - Iis Uswatun Hasanah; Yuwan Fijar Anugrah; Annisa Purwani (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2025)
Basic literacy and numeracy skills are an important investment in a child's future. Efforts to develop these abilities from an early age will provide long-term benefits for children's cognitive, social and academic development. This community service aims to improve basic literacy and numeracy skills in early childhood at SPS Melati II, Margasari Village, Pasawahan District through market day activities. This activity is a learning innovation that actively involves children as sellers and buyers, and uses menu books as a medium for offering products. This research used the Participant Action Research (PAR) method with research subjects of 21 early childhood who participated in this activity, as well as teachers and parents who were involved in market day activities. Observation results show that market days are effective in improving children's literacy and numeracy skills, such as the ability to read food names, calculate the amount of groceries, and interact with peers. This activity also provides a fun and meaningful learning experience for early childhood